118k views
2 votes
F(x)=4x+2


3[f(-2)]= ?

(please leave steps below)

User Lucasls
by
5.6k points

2 Answers

4 votes
You're gonna start with "[f(-2)]" cuz pemdas.

"f(-2)" means you're gonna replace every "x" in the equation with "-2"

f(x)=4(-2)+2

Now multiply then add

f(x)=-6

so now you can go back to the second equation and replace [f(-2)] with -6

3[-6]

and multiply:

-18
User Ickster
by
5.8k points
3 votes
F(-2)=4x+2
F(-2)=4(-2)+2
F(-2)=-8+2
F(-2)=-6
3{F(-2)}=3(-6)
FINAL ANSWER: -18
User GrandFleet
by
5.2k points